MitoSOX-Based Flow Cytometry for Detecting Mitochondrial ROS - Kauffman, Megan E. (React Oxyg Species (Apex), 2016)
MitoSOX-based assays are widely used to detect mitochondrial reactive oxygen species (ROS), especially superoxide. To this end, 5 μM MitoSOX is commonly used. In this ROS Protocols article, we described the flow cytometric protocol involving the use of various concentrations of MitoSOX (1, 2.5, 5 μM) for detecting mitochondrial ROS in control and mitochondrial DNA-deficient (MD) melanoma B16-F10 cells. We also compared the MitoSOX-based flow cytometry with lucigenin-derived chemiluminometry for their ability to reliably detect the relative differences in mitochondrial ROS formation in the control and MD cells. Our results suggested that 1 μM, rather than the commonly used 5 μM, appeared to be the optimal concentration of MitoSOX for detecting mitochondrial ROS via flow cytometry.